Worker rehabilitation programs. Separating fact from fiction. - Haig, A. J. (1991)
A few worker rehabilitation programs have had outstanding success in improving ability to function for persons with occupational back pain. Local programs must show that they have similar success. Because the definitions of terms such as "back school," "work hardening," and "functional restoration" are blurred at a local level, the choice of a program for an individual patient must depend primarily on the program's demonstrated success rate with similar patients. The chances of returning to work decrease as a function of time after injury. Therefore, referring physicians, insurers, and employers must be provided with information regarding results in terms of acute (0 to 6 weeks), subacute (7 to 12 weeks), and chronic (more than 12 weeks) back pain. Other important variables include selection criteria, program cost, and dropout rate. We advocate standardized reporting of such data for all worker rehabilitation programs. A model "report to consumers," described here, is a minimal obligation. The validity of a number of important internal quality assurance issues is uncertain. Ethical and legal pressures must be recognized.